Electronis Discussion
0 votes

The general solution of $\dfrac{\mathrm{d^{2}} y}{\mathrm{d} x^{2}}-6\dfrac{\mathrm{d} y}{\mathrm{d} x}+9y=0$ is

  1. $y=C_{1}e^{3x}+C_{2}e^{-3x}$
  2. $y=(C_{1}+C_{2}x)e^{-3x}$
  3. $y=(C_{1}+C_{2}x)e^{3x}$
  4. $y=C_{1}e^{3x}$
in Others by (1.4k points)
edited ago by

Please log in or register to answer this question.

Answer:
Welcome to GO Electronics, where you can ask questions and receive answers from other members of the community.
1,109 questions
58 answers
8 comments
43,176 users